Fabrication of Bio-Functionalised Polypyrrole Nanoarrays for Bio-Molecular Recognition - Lisboa, Patricia; Villiers, Marie-Bernadette; Brakha, Carine; N. Marche, Patrice; Valsesia, Andrea; Colpo, Pascal; Rossi, Francois (Micro and Nanosystems, 2011)
The present study demonstrates that nanosphere lithography and electro-polymerization can be successfully combined to produce bioactive protein nanoarrays. In particular, we describe a method to produce well-defined nanoarrays of polypyrrole functionalized with biomolecules. The nanoarrayed surfaces were fabricated on gold coated surface plasmon resonance prisms by first creating silicon oxide or polyethylene oxide nanotemplate using nanosphere lithography. The nanotemplate was subsequently used to grow bio-functionalized polypyrrole nanoarrays by electrocopolymerization. Atomic force microscopy analysis showed that the fabricated surfaces have a well-organized 2D hexagonal geometry with nanoscale dimensions. The biological activity of the bio-functionalized polypyrrole was assessed by surface plasmon resonance detection. The results showed that the immobilized biomolecules within the nanoarrayed polypyrrole films had the necessary bioactivity for successful molecular recognition. Moreover the detection signals normalized to the bioactive area were increased by a factor 5 as compared to non-structured bio-functionalized polypyrrole in the nanoarrayed surfaces using polyethylene oxide.
Keywords: Colloidal lithography